PERLINDUNGAN HUKUM TERHADAP PENDAFTAR MEREK PERTAMA ACC MEMBERI KEMUDAHAN MENURUT UU 20 TAHUN 2016 (CONTOH KASUS SENGKETA ANTARA PT ASTRA SEDAYA FINANCE DENGAN PT AMAN CERMAT CEPAT TERKAIT PERSAMAAN MEREK TAHUN 2019) - Ellohim Theo Sentana; Simona Bustani (Jurnal Hukum Adigama, 2019)
The Panel of Judges of the Central Jakarta District Court (PN Jakpus), handed down a ruling that rejected some of the petitum lawsuit of PT Astra Sedaya Finance related to its brand equality 'ACC makes it easy' with a trademark owned by PT Aman Cermat Rapid, namely 'Klik ACC '. In his statement, stating that the plaintiff had a good intention in registering the ACC mark made it easy. Stating ACC makes it easy is a brand with a good reputation. Rejecting the plaintiff's lawsuit after comparing the plaintiff's and the defendant's trademark forms, the Assembly is of the opinion that there is no resemblance between the brand of PT Astra Sedaya Finance with the brand of PT Aman Cermat Cepat. The ACC business identity eventually developed into the brand 'ACC makes it easy', which was even registered in 2014 with the certificate brand No. IDM000554835 for class 36, which is the class of goods / services. Meanwhile, he said, PT ACC just registered the trademark on April 10, 2018 with a certificate. Considering that the ACC brand makes it easy to be officially registered on June 26, 2014, said Fajar, it means that the protection of the trademark rights will only be exhausted on June 26, 2024. That, too, if the time period runs out can still be extended for the same time period.